TRADISI RIHLAH ‘ILMIYYAH DI KALANGAN ULAMA HADIS - Nirwana, Dzikri (Jurnal Studia Insania, 2015)
The tradition of hijrah seek knowledge often referred to as the ?ilmiyyah rihlah travel or study that has been inherited by those earlier (the salaf al-shâlih) to the current generation. This paper specifically highlights the rihlah ?ilmiyyah tradition among the scholars of Hadith in historical perspective. The presence technological advances and information now that it?s been more advanced, as well as easily accessible online anytime and any where, does not mean rihlah ? ilmiyyah by the time this becomes less relevant again. However, because a meeting directly with the teachers remain necessary in order to keep the scientific ethics and objectivity of scholarship which in turn will generate sustainable goodness value, or in the language of religion is referred to as the ?blessing ? of science. This was the movitasi scholars of classical tradition to keep doing this to perlawatan seeking other areas, despite having to go through the difficulties and obstacles.